Complex biochemical characteristics of Coriandrum sativum L. - T. V. Khmelinskaya; A. E. Smolenskaya; A. E. Solovyeva (Труды по прикладной ботанике, генетике и селекции, 2021)
Background.  Coriandrum sativum L. is a valuable vegetable crop with early maturity and high nutritional benefits. Green biomass of coriander is rich in vitamins, especially ascorbic acid and carotene. The feasibility of using coriander as a natural food additive is due to its high antioxidant activity. The aim of this research was to study the biochemical composition of the green biomass in the accessions of C. sativum from the VIR global collection and identify promising accessions for use in breeding for quality.Materials and methods. The green biomass of  67 coriander accessions from different countries maintained in the VIR collection served as the research material. The study was carried out according to the guidelines developed by VIR.Results. As a result of the study, the feasibility of using C. sativum as a source of bioactive compounds was theoretically justified and experimentally confirmed, thus attesting to the prospects of coriander accessions from the VIR collection for quality-targeted breeding programs. New data were obtained on the biochemical composition of coriander green biomass. A factor determining such biochemical composition is the genotypic features of coriander associated with its origin. Biochemical parameters in coriander varied significantly depending on the origin of an accession. The highest variability was observed in the content of carotenes (CV 41%). The effect of an accession’s precocity was not confirmed. Sources for individual quality indicators were highlighted.Conclusion. Accessions with an optimal component composition for a balanced human diet were identified and recommended for quality-oriented breeding, including the development of cultivars for health-friendly, curative and preventive nutrition. The selected accessions are of interest as source material for breeding programs and practical utilization.